Prevalence and Factors Associated with Depressive Symptoms in Mothers with Infants or Toddlers - Hua-Pin Chang; Jia-Yuh Chen; Yen-Hsun Huang; Jeng-Yi Tyan; Chih-Jung Yeh; Pan-Hua Su; Vincent Chin-Hung Chen (Pediatrics and Neonatology, 2014)
The objective of this study is to explore the prevalence of and factors associated with depressive symptoms in mothers with young children. Methods: This is a cross-sectional face-to-face study performed between January 1, 2010 and June 30, 2011. Mothers of premature infants with a gestational age of less than 37 weeks were recruited. Premature infants with any congenital anomaly or severe congenital heart disease were excluded. Controls were mothers of full-term infants with birth weight over 2500 g and without admission to a neonatal intensive care unit. Outcome measures included the Center for Epidemiologic Studies Depression Scale for maternal depressive symptoms, the Family Apgar Index for family support, and the Chinese Maudsley Personality Inventory for personality traits. Results: A total of 102 mothers of preterm infants and 111 mothers of full-term infants were recruited. The prevalence of depressive symptoms was 27.7% (59/213) in all mothers of this study, 29.4% (30/102) in mothers of preterm infants, and 26.1% (29/111) in mothers of full-term infants. Predictors of maternal depressive symptoms included the following: extended family structure, lack of postpartum confinement, low family support, and a personality characterized by neuroticism. Conclusion: Depressive symptoms were common among mothers of young children. Family function and neurotic personality were highly correlated with depressive symptoms in mothers caring for young children. Pediatric health care providers are suggested to screen for maternal depressive symptoms and provide family-oriented support in Taiwan.